Reliability analysis of vehicle speed estimation based on uncertainty of information obtained on accident scene. Issue 4 (4th July 2019) - Zhang, Xiaoyun; Zhang, Dongming; Yang, Xiaobo; Hou, Xinyi
Abstract: In numerical analysis of vehicle–pedestrian accidents, the estimation of impact speed is often completed based on some on-scene information such as pedestrian projection distance. In this article, aimed at the uncertainty of accident on-scene information, error calculation formulas of crucial information are derived based on the process of on-scene investigation. Meanwhile, the reliability model of pedestrian projection distance measurement is established using first-order reliability method. With the vehicle–pedestrian accident scene that has been built, the reliability safety factors of projection distance measurement under different impact velocity are calculated. Furthermore, the influence of positioning methods, impact velocity, and datum points on reliability of on-scene information is discussed, and some suggestions are made to improve the reliability of on-scene investigation.